2018
DOI: 10.3389/fphys.2018.01225
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Black Tea Extract and Thearubigins on Osteoporosis in Rats and Osteoclast Formation in vitro

Abstract: Background: Osteoporosis is a major health problem that is closely related to substantial morbidity, mortality and decline in life quality for the aging population. Although previous studies and epidemiological evidence have demonstrated an association between black tea consumption and the prevention of bone loss, the underlying mechanism remains unclear. So, the effect of black tea extract (BTE) and thearubigins (TRs) on osteoporosis in rats and osteoclast formation in vitro were investigated.Methods: In vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
2
12
0
1
Order By: Relevance
“…To better understand the direct effects of both "true teas" and herbals on bone formation and resorption, osteoblast, and osteoclast cell models have also been used. In both osteoblast and osteoclast models, cells supplemented with black or green tea or specific polyphenols present in these teas have consistently shown positive effects as measured by increased mineral formation [30][31][32] and reduced bone resorption [33,34]. Previously, two different concentrations of green rooibos tea (1 and 10 µg/mL of polyphenols) had been tested in an osteoblast cell model [32].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the direct effects of both "true teas" and herbals on bone formation and resorption, osteoblast, and osteoclast cell models have also been used. In both osteoblast and osteoclast models, cells supplemented with black or green tea or specific polyphenols present in these teas have consistently shown positive effects as measured by increased mineral formation [30][31][32] and reduced bone resorption [33,34]. Previously, two different concentrations of green rooibos tea (1 and 10 µg/mL of polyphenols) had been tested in an osteoblast cell model [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that tea decoctions and extracts can therapeutically alleviate osteolytic bone loss. 12,13 Although purple tea (Zijuan tea) extracts shown to possess many health benefits, such as anti-inflammatory, anti-proliferative, and anti-oxidative stress characteristics, 14,28 its effects on osteoclast formation have not yet been reported. In this study, we demonstrated that a water-based extract of purple tea could effectively inhibit RANKL-induced osteoclastogenesis in vitro while also reducing bone degradation in vivo in LPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…10 Due to their rich antioxidant components, tea-based beverages exhibit enormous salutary properties for improving human health, as demonstrated in numerous previously reported investigations of anti-osteolytic properties of green tea or black tea extracts. [11][12][13] Purple tea, also known as Zijuan tea (Camellia sinensis var. kitamura), is known for its purple leaves, stems, and buds and abundant nutrients and beneficial components, such as anthocyanins, polyphenols, zinc, caffeine, and many others.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of tea and its specific polyphenols on both osteoblasts and osteoclasts have been studied using cell models. [11][12][13][14][15][16][17][18][19] The majority of studies using osteoblasts have studied the effects of green or black teas and have consistently shown increases in mineralization in response to tea. More specifically black, green, and rooibos (red and green) teas have been shown to increase mineralization at concentrations likely attainable through diet.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] While studies in osteoclasts are limited, previously published studies have shown that black, green, or green rooibos teas elicit a decrease in activity. [17][18][19] The majority of literature has investigated green and black teas. Based on current trends of tea consumption in the Canadian market, information regarding the influence of specialty teas on health, including bone health, may further increase interest among consumers.…”
Section: Introductionmentioning
confidence: 99%